2015
DOI: 10.1128/jvi.03688-14
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Inhibitors against 3C-Like Proteases of Feline Coronaviruses and Feline Caliciviruses

Abstract: Feline infectious peritonitis and virulent, systemic calicivirus infection are caused by certain types of feline coronaviruses (FCoVs) and feline caliciviruses (FCVs), respectively, and are important infectious diseases with high fatality rates in members of the Felidae family. While FCoV and FCV belong to two distinct virus families, the Coronaviridae and the Caliciviridae, respectively, they share a dependence on viral 3C-like protease (3CLpro) for their replication. Since 3CLpro is functionally and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(144 citation statements)
references
References 40 publications
8
131
0
1
Order By: Relevance
“…These findings indicate that A252S and K260 N mutations do not affect the susceptibility of 3CLpro against GC376. NPI52 is a tripeptidyl compound that shares a similar backbone structure with GC376 and has a similarly potent activity against feline coronavirus as GC376 in the FRET assay and cell culture (Kim et al, 2015). However, unlike those of GC376, there was no difference in the IC 50 values of 3CLpro with WT, single, double or triple mutations against NPI52 (Fig.3A and B).…”
Section: The Effects Of Amino Acid Changes In 3clpro Against Gc376mentioning
confidence: 94%
See 1 more Smart Citation
“…These findings indicate that A252S and K260 N mutations do not affect the susceptibility of 3CLpro against GC376. NPI52 is a tripeptidyl compound that shares a similar backbone structure with GC376 and has a similarly potent activity against feline coronavirus as GC376 in the FRET assay and cell culture (Kim et al, 2015). However, unlike those of GC376, there was no difference in the IC 50 values of 3CLpro with WT, single, double or triple mutations against NPI52 (Fig.3A and B).…”
Section: The Effects Of Amino Acid Changes In 3clpro Against Gc376mentioning
confidence: 94%
“…The https://doi.org/10.1016/j.vetmic.2019.108398 Received 10 July 2019; Received in revised form 21 August 2019; Accepted 21 August 2019 released viral proteins form the replicase-transcriptase complex, which is required for RNA replication and transcription of the subgenomic RNAs, thus inhibition of viral proteases blocks viral replication. We have previously reported the synthesis of protease inhibitors for feline coronavirus (Kim et al, 2012a(Kim et al, , 2013Kim et al, 2015), and showed the efficacy of one of the inhibitors, GC376, in cats with experimentally induced FIP (Kim et al, 2016) and naturally-occurring FIP in a field trial (Pedersen et al, 2018). We have also reported the amino acid changes (N25S, A252S and K260 N) in the 3CLpro of feline coronavirus collected from a patient who was treated with GC376 but did not show clinical resistance to multiple rounds of treatment in the field trial (Pedersen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, many reports showed that Mpro is an ideal target for drug design and development (34)(35)(36). The well-characterized inhibitors of Mpro can be classified into 2 classes based on their chemical structures.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-protease inhibitors approved for viral infection treatment are interesting examples in this connection. Recently, these inhibitors are screened for their capability to inhibit Mpro and treat SARS infection using in vivo, in vitro, and in silico experiments (34)(35)(36)(37)(38)(39). The clinical trial of LPV showed a significant decrease in virus titer, reduced rate of death, and improved clinical recovery (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Rupintrivir for instance is an irreversible 3C-protease inhibitor that was originally developed for the treatment of human rhinovirus infections [22] and antiviral activity has also been shown against other picornaviruses, coronaviruses, and norovirus [23][24][25]. Other inhibitors of 3C-like proteases were reported with broad-spectrum antiviral activity against both feline coronaviruses and caliciviruses [26]. Therefore, the design of BSAA targeting proteases of different virus families appears feasible and could be a good strategy to develop broader-spectrum antivirals.…”
Section: Viral Protease Inhibitorsmentioning
confidence: 97%